Preparation method of aldehyde cellulose nanoparticles with high dispersion stability
Aldehyde-based cellulose nanoparticles are prepared by mixing sodium periodate, cellulose nanocrystals and zinc chloride in an aqueous solution system, which solves the problem of low dispersion stability of cellulose nanoparticles and achieves higher stability and effectiveness in biological applications.
Patent Information
- Application Number
- CN202411876152.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-14
AI Technical Summary
The dispersion stability of existing cellulose nanoparticles is low, making it difficult to maintain stability and effectiveness in biological applications.
In the aqueous solution system, sodium periodate, cellulose nanocrystals and zinc chloride are mixed to react, the reaction time and temperature are adjusted, and the aldehyde-based cellulose nanoparticles are prepared to improve their dispersion stability.
Through aldehyde synthesis treatment, the dispersion stability of cellulose nanoparticles is improved, their stability in salt solutions and polar organic solvents is enhanced, and their stability in the biological environment is extended.
Smart Images

Figure CN119613575A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of cellulose modification, and in particular to a method for preparing cellulose nanoparticles with high dispersion stability. Background Art
[0002] The delivery and targeting of nanocarriers is an important research direction in nanomedicine. Currently, commonly used nanocarriers include liposomes, polymers, mesoporous nanoparticles, polymer nanoparticles, magnetic nanoparticles, colloidal gold and carbon nanotubes. However, the development of some nanoparticle carriers is limited by metal impurities, particle aggregation, long-term instability, difficulty in penetrating cell membranes and cytotoxicity. In addition, due to the presence of a large number of proteins in the blood environment, they will spontaneously adsorb to the surface of nanoparticle carriers, resulting in the formation of protein coronas, thereby changing the colloidal stability, adsorption, targeting, bioreactivity and toxicity of nanoparticle carriers. For most nanomaterials with relatively large particle sizes (≥10nm), especially those that are not biodegradable, high uptake by the reticuloendothelial system (RES) leads to low in vivo clearance efficiency and potential long-term toxicity to the body. Therefore, it is highly desirable to give nanocarriers dynamically adjustable physicochemical properties (such as geometry and surface chemistry) to overcome physiological barriers at multiple stages of the delivery process. Coating materials with the ability to inhibit specific protein adsorption, such as polyethylene glycol (PEG), poly(zwitterions), polyphosphates, and poly(oxazolines), enable nanocarriers to evade phagocytosis by the liver.
[0003] Cellulose nanocrystals are a new type of cellulose composition material with unique rod-like shape (average aspect ratio of 10-100), high hydrophilicity, good modifiability and biodegradability, which has aroused increasing interest in the design of advanced functional biomaterials. The large number of hydroxyl groups on the cellulose surface bring active sites, making cellulose nanocrystals easy to functionalize or biocouple, thus providing new materials and platforms for a variety of biological applications. In recent years, different types of cellulose-based nanomaterials have been studied, but they are mainly focused on the cellular level, which requires high dispersion stability of cellulose nanoparticles. Summary of the invention
[0004] Purpose of the invention: In view of the problem of low dispersion stability of existing cellulose nanoparticles, the present invention provides a method for preparing cellulose nanoparticles with high dispersion stability.
[0005] Technical solution: To achieve the above purpose, the technical solution adopted by the present invention is:
[0006] A method for preparing aldehyde-modified cellulose nanoparticles with high dispersion stability comprises the following steps: in an aqueous solution system with a reaction temperature of 40-45°C and a pH value of 3-4, mixing cellulose nanocrystals with sodium periodate and zinc chloride for reaction, and adjusting the reaction time to obtain aldehyde-modified cellulose nanoparticles with high dispersion stability.
[0007] Preferably, the weight components of the reactants are: 100 parts of water, 0.5-2 parts of cellulose nanocrystals, 3-12 parts of sodium periodate, and 0.5-2 parts of zinc chloride.
[0008] Preferably, the reaction time is 2 to 60 hours.
[0009] Preferably, the cellulose nanocrystals are rod-shaped nanomaterials produced by hydrolysis of bleached softwood pulp or microcrystalline cellulose with hydrochloric acid or sulfuric acid; the cellulose nanocrystals have a length in the range of 200 to 300 nm, a diameter in the range of 5 to 10 nm, and an aspect ratio in the range of 60 to 20.
[0010] Preferably, the surface aldehyde content of the aldehyde-modified cellulose nanoparticles is 1 to 5 mmol·g -1 .
[0011] Preferably, the aldehyded cellulose nanoparticles are rod-shaped or spherical, have a size gradient change characteristic, a length in the range of 30 to 200 nm, a diameter in the range of 5 to 10 nm, and an aspect ratio in the range of 20 to 1.1.
[0012] Preferred: Concentration 0.1-2 mg·mL -1 Aldehyde cellulose nanoparticles can be used in the presence of 0.01-0.05 mol·L -1 The nanoparticles are stably dispersed in sodium chloride aqueous solution within the PBS concentration range. The concentration of sodium chloride solution is related to the aldehyde content and size of the cellulose nanoparticles. The higher the aldehyde content, the smaller the size and the higher the concentration of the salt solution.
[0013] Preferred: Concentration 0.1-2 mg·mL -1 Aldehyde-modified cellulose nanoparticles can be stably dispersed in polar organic solvent systems; the stably dispersed organic solvents include one or a mixture of two or more of dimethyl sulfoxide, N,N-dimethylformamide, formic acid, acetic acid, methanol, ethanol, and tetrahydrofuran. The range of organic solvents is related to the aldehyde content and size of the cellulose nanoparticles. The higher the aldehyde content, the smaller the size, and the lower the dielectric constant of the organic solvent.
[0014] Preferably: the freeze-dried aldehyde-modified cellulose nanoparticles can be stably dispersed in water and polar organic solvents at a concentration of 0.1 to 2 mg mL -1The range of redispersible stable polar organic solvents includes one or more mixed solvents of water, dimethyl sulfoxide, N,N-dimethylformamide, formic acid, acetic acid, methanol, ethanol, and tetrahydrofuran. The dispersible concentration of cellulose nanoparticles is related to the aldehyde content and size of the cellulose nanoparticles and the constant of the solvent. The higher the aldehyde content, the smaller the size, the higher the dielectric constant of the organic solvent, and the higher the dispersible concentration of cellulose nanoparticles.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] 1. Sodium periodate, cellulose nanocrystals and zinc chloride are mixed and reacted in an aqueous solution system. Due to the hydrolysis of the acid on the fiber and the weakening of the hydrogen bonds in the fiber by the metal salt, a certain degree of CNC cutting and molecular reorganization of the cellulose nanocrystals are achieved, while at the same time ensuring that the cellulose is not over-hydrolyzed into monosaccharides, so that the aldehyde content in the obtained aldehyde-modified cellulose nanoparticles is high, and therefore its dispersion stability is high.
[0017] 2. In addition, since the oxidation of vicinal diols produces aldehyde groups, the hydrogen bonding between fibers is greatly reduced, so that the obtained aldehyde-modified cellulose nanoparticles have high redispersion stability.
[0018] 3. Aldehydated cellulose nanoparticles have high salt solution dispersion stability; in particular, the stability to PBS buffered saline solution is particularly outstanding. During the 5-day test period, the hydrodynamic radius of the nanoparticles did not undergo any significant change.
[0019] 4. By adjusting the reaction time and temperature, the preparation of cellulose nanoparticles with different aldehyde contents and different sizes can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The Tyndall effect image of aldehyde-modified cellulose nanoparticles with high dispersion stability dispersed in acetone before and after oxidation;
[0021] Figure 2 Tyndall effect image of redispersion of aldehyde-modified cellulose nanoparticles with high dispersion stability in water before and after oxidation;
[0022] Figure 3 is a schematic diagram of the reaction mechanism, where Figure 3 Figure a is a diagram showing the mechanism of hydrated zinc ions promoting periodate oxidation of cellulose. Figure 3 Figure b is a diagram showing the mechanism of aldehyde-modified cellulose nanoparticles inhibiting inter-particle hydrogen bonding;
[0023] Figure 4 is the XRD change spectrum of cellulose nanoparticles under different oxidation times;
[0024] Figure 5is the UV absorption variation spectrum of cellulose nanoparticles at different oxidation times;
[0025] Figure 6 is the TEM morphology characterization of cellulose nanoparticles at different oxidation times;
[0026] Figure 7 is the size change of cellulose nanoparticles under different oxidation times. DETAILED DESCRIPTION
[0027] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.
[0028] Example 1
[0029] A method for preparing cellulose nanoparticles with high dispersion stability comprises the following steps:
[0030] In a 100 mL aqueous solution system, the pH value is adjusted to 3.5 by acetic acid / sodium acetate buffer, and 1 g of cellulose nanocrystals, 6 g of sodium periodate, and 1 g of zinc chloride are mixed at 45 ° C for reaction. The cellulose nanocrystals are rod-shaped nanomaterials produced by hydrochloric acid hydrolysis of microcrystalline cellulose. The length of the cellulose nanocrystals is in the range of 200-300 nm, the diameter is in the range of 5-10 nm, and the aspect ratio is in the range of 60-20. The reaction time is different (2h, 4h, 6h, 8h, 10h, 12h, 14h, 24h, 48h, 60h), and then dialysis (MWCO: 10kDa) is performed for at least 3 days until the conductivity of the external dialysis solution remains unchanged. Finally, the sample is freeze-dried and stored in a dry environment to obtain aldehyde-modified cellulose nanoparticles with high dispersion stability and size gradient change (different sizes), named DACn, where n is the reaction time. The obtained aldehyde-modified cellulose nanoparticles are rod-shaped or spherical, with a size gradient change characteristic, a length in the range of 30 to 200 nm, a diameter in the range of 5 to 10 nm, an aspect ratio in the range of 20 to 1.1, and a surface aldehyde content in the range of 1 to 5 mmol·g -1 .
[0031] Example 2
[0032] The difference between this embodiment and embodiment 1 is that the pH value is adjusted to 3 by acetic acid / sodium acetate buffer, and 2 g of cellulose nanocrystals, 12 g of sodium periodate, and 2 g of zinc chloride are mixed and stirred at 40° C. Cellulose nanocrystals are rod-shaped nanomaterials produced by hydrolyzing microcrystalline cellulose with sulfuric acid.
[0033] Example 3
[0034] The difference between this embodiment and embodiment 1 is that the pH value is adjusted to 4 by acetic acid / sodium acetate buffer, and 0.5 g of cellulose nanocrystals, 3 g of sodium periodate, and 0.5 g of zinc chloride are mixed and stirred at 42° C. Cellulose nanocrystals are rod-shaped nanomaterials produced by hydrolysis of bleached softwood pulp with hydrochloric acid.
[0035] Concentration: 1 mg mL -1 Aldehyde-modified cellulose nanoparticles can be stably dispersed in sodium chloride aqueous solution with a concentration range of 0.01 to 0.05 times the PBS concentration. The concentration of the sodium chloride solution is related to the aldehyde content and size of the cellulose nanoparticles. The higher the aldehyde content, the smaller the size and the higher the concentration of the salt solution. -1 Aldehyde-modified cellulose nanoparticles can be stably dispersed in polar organic solvent systems; the organic solvents for stable dispersion include one or a mixture of two or more of dimethyl sulfoxide, N,N-dimethylformamide, formic acid, acetic acid, methanol, ethanol, and tetrahydrofuran. The range of organic solvents is related to the aldehyde content and size of the cellulose nanoparticles. The higher the aldehyde content, the smaller the size, and the lower the dielectric constant of the organic solvent. Figure 1 As shown, it is a dispersion picture of the formaldehyde-modified cellulose nanoparticles with high dispersion stability obtained by reacting for 12 hours in Example 1 of the present invention before and after oxidation in acetone for 24 hours. It can be seen from the figure that compared with the cellulose nanocrystals before oxidation, the formaldehyde-modified cellulose nanoparticles after oxidation can be well dispersed in acetone.
[0036] The freeze-dried aldehyde-modified cellulose nanoparticles can be stably redispersed in water and polar organic solvents at a concentration of 0 to 1 mg mL -1 The range of redispersible polar organic solvents includes water, dimethyl sulfoxide, N,N-dimethylformamide, formic acid, acetic acid, methanol, ethanol, tetrahydrofuran, or a mixture of two or more. The dispersible concentration of cellulose nanoparticles is related to the aldehyde content and size of the cellulose nanoparticles and the constant of the solvent. The higher the aldehyde content, the smaller the size, the higher the dielectric constant of the organic solvent, and the higher the dispersible concentration of cellulose nanoparticles. Figure 2 As shown, it is a redispersion picture of the aldehyde-sylated cellulose nanoparticles with high dispersion stability obtained after 12 hours of reaction in Example 1 of the present invention, which is redispersed in water after a dispersion time of 24 hours. It can be seen from the figure that compared with the cellulose nanocrystals before oxidation, the aldehyde-sylated cellulose nanoparticles after oxidation can be well redispersed in water.
[0037] The concentration of the aldehyde-modified cellulose nanoparticles with high dispersion stability is 0-1 wt %. The length of the aldehyde-modified cellulose nanoparticles with high dispersion stability and size gradient change is 30-200 nm, and the shape is spherical or rod-like.
[0038] like Figure 3 As shown in FIG. 1 , it is a schematic diagram of the reaction mechanism of cellulose nanoparticles with high dispersion stability in this embodiment. Figure 3 As shown in Figure a, zinc chloride generates hydrated zinc ions in an aqueous system, which can react with the hydroxyl groups of cellulose to generate cellulose hydroxyl groups bound by hydrated zinc ions, thereby inhibiting the formation of hydrogen bonds within and between fibers, reducing the interaction between fibers and facilitating the entry of the reaction reagent molecules; on the other hand, the activation energy of the reaction between the cellulose hydroxyl groups bound by hydrated zinc ions and sodium periodate is reduced, which can promote the oxidation of the fiber vicinal diols and increase the reaction efficiency. Figure 3 As shown in Figure b, due to the oxidation of vicinal diols to produce aldehyde groups, the aldehyde-modified cellulose nanoparticles inhibit the hydrogen bonds between particles and greatly reduce the hydrogen bonding between fibers, making the obtained aldehyde-modified cellulose nanoparticles have high redispersion stability.
[0039] like Figure 4-7 As shown in the figure, the XRD change spectrum, UV absorption change spectrum, TEM morphology characterization and size change of the cellulose nanoparticles obtained in Example 1 at different oxidation times, while producing cellulose nanoparticles of different sizes, a large number of aldehyde groups (1-5 mmoL·g -1 ), since the aldehyde group lacks the -OH group compared to the carboxyl or hydroxyl group, it is more difficult to form hydrogen bonds, which greatly reduces the ability of hydrogen bonds between fibers and inhibits the aggregation of fibers.
[0040] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing aldehyded cellulose nanoparticles with high dispersion stability, characterized in that: In an aqueous solution system with a reaction temperature of 40-45° C. and a pH value of 3-4, cellulose nanocrystals are mixed with sodium periodate and zinc chloride for reaction, and the reaction time is adjusted to obtain aldehyde-modified cellulose nanoparticles with high dispersion stability.
2. The method for preparing aldehyded cellulose nanoparticles with high dispersion stability according to claim 1, characterized in that: The weight components of the reactants are: 100 parts of water, 0.5-2 parts of cellulose nanocrystals, 3-12 parts of sodium periodate, and 0.5-2 parts of zinc chloride.
3. The method for preparing aldehyded cellulose nanoparticles with high dispersion stability according to claim 2, characterized in that: The reaction time is 2 to 60 hours.
4. The method for preparing aldehyded cellulose nanoparticles with high dispersion stability according to claim 3, characterized in that: The cellulose nanocrystal is a rod-shaped nano material produced by hydrolyzing bleached softwood pulp or microcrystalline cellulose with hydrochloric acid or sulfuric acid; the cellulose nanocrystal has a length in the range of 200-300nm, a diameter in the range of 5-10nm, and an aspect ratio in the range of 60-20.
5. The method for preparing aldehyded cellulose nanoparticles with high dispersion stability according to claim 4, characterized in that: The surface aldehyde content of aldehyde-modified cellulose nanoparticles is 1-5 mmol·g -1 .
6. The method for preparing aldehyded cellulose nanoparticles with high dispersion stability according to claim 5, characterized in that: The aldehyded cellulose nanoparticles are rod-shaped or ellipsoidal, have the characteristics of size gradient change, have a length in the range of 30 to 200 nm, a diameter in the range of 5 to 10 nm, and an aspect ratio in the range of 20 to 1.
1.
7. The method for preparing aldehyded cellulose nanoparticles with high dispersion stability according to claim 6, characterized in that: Concentration 1 mg mL -1 Aldehyde cellulose nanoparticles can be used in the presence of 0.01-0.05 mol·L -1 It is stably dispersed in sodium chloride aqueous solution within the PBS concentration range.
8. The method for preparing aldehyded cellulose nanoparticles with high dispersion stability according to claim 7, characterized in that: Concentration: 0.1-2 mg mL -1 The aldehyde-modified cellulose nanoparticles can be stably dispersed in a polar organic solvent system; the stably dispersed organic solvent includes one or a mixed solvent of two or more of dimethyl sulfoxide, N,N-dimethylformamide, formic acid, acetic acid, methanol, ethanol, and tetrahydrofuran.
9. The method for preparing aldehyded cellulose nanoparticles with high dispersion stability according to claim 8, characterized in that: The freeze-dried aldehyde-modified cellulose nanoparticles can be stably redispersed in water and polar organic solvents at a concentration of 0.1 to 2 mg mL -1 The redispersible polar organic solvent includes one or a mixed solvent of two or more of water, dimethyl sulfoxide, N,N-dimethylformamide, formic acid, acetic acid, methanol, ethanol and tetrahydrofuran.